2015
DOI: 10.1007/s00404-015-3692-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety of insulin analogs during pregnancy: a meta-analysis

Abstract: Aspart, glargine, and detemir are safe treatment options for diabetes during pregnancy; these insulin analogs did not increase complications for the mothers or fetuses in our study. However, lispro was related to higher birth weight and increased rate of LGA in neonates. More high-quality randomized controlled trials are needed to clarify the best treatment options for diabetes during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 36 publications
3
43
0
6
Order By: Relevance
“…They reported no significant difference in the maternal and neonatal outcomes in patients using aspart, glargine, and determir. However, insulin lispro was associated with higher birth weight and an increased rate of LGA newborns, similar to the findings of the previous meta-anaylsis [33].…”
Section: Lisprosupporting
confidence: 88%
See 3 more Smart Citations
“…They reported no significant difference in the maternal and neonatal outcomes in patients using aspart, glargine, and determir. However, insulin lispro was associated with higher birth weight and an increased rate of LGA newborns, similar to the findings of the previous meta-anaylsis [33].…”
Section: Lisprosupporting
confidence: 88%
“…They also found higher rate of macrosomia in the lispro group (14.5%) compared to regular insulin (11.5%), although the increase was not significant [26]. The two meta-analysis published by Gonzalez et al [32] and Lv et al [33] both reported an increased rate of LGA newborns, along with increased birth weight in the latter. The earlier study only included four studies and limited to T1DM, which does not fully provide compelling evidence.…”
Section: Lispromentioning
confidence: 92%
See 2 more Smart Citations
“…It was also shown to result in similar overall glycaemic control and neonatal outcomes when compared with short-acting (regular) insulin [19]. In contrast, a meta-analysis of observational studies using insulin lispro concluded that its use during pregnancy is associated with a decrease in severe maternal hypoglycaemia and a decrease in hyperbilirubinaemia in infants, but it is also associated with an increase in infants born LGA [20]. Of the long-acting insulins, only insulin detemir and insulin glargine have been studied during pregnancy.…”
Section: Therapeutic Approaches For Pregnant Women With Diabetesmentioning
confidence: 99%